2019
DOI: 10.1111/nep.13252
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between incremental and thrice‐weekly haemodialysis: Systematic review and meta‐analysis

Abstract: An incremental therapeutic approach as a beginning HD regimen is associated with lower mortality and better preservation of greater residual renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
3
20
1
1
Order By: Relevance
“…A recent meta-analysis has reported a risk reduction of 20% with incremental dialysis [9]. However, this remains controversial [14], without any available RCT and possible bias by indication when twice-weekly HD is implemented for economic matters or/and in patients younger DOI: 10.1159/000494582 with less comorbidities as reported by Lindenfeld et al [15].…”
Section: Does Twice-weekly Dialysis Reduce Early Mortality Of Incidenmentioning
confidence: 95%
See 4 more Smart Citations
“…A recent meta-analysis has reported a risk reduction of 20% with incremental dialysis [9]. However, this remains controversial [14], without any available RCT and possible bias by indication when twice-weekly HD is implemented for economic matters or/and in patients younger DOI: 10.1159/000494582 with less comorbidities as reported by Lindenfeld et al [15].…”
Section: Does Twice-weekly Dialysis Reduce Early Mortality Of Incidenmentioning
confidence: 95%
“…Because the short daily Frequent Hemodialysis Network trial has reported a 78% increase of vascular access interventions with 6-weekly short HD sessions compared to standard HD [52], several papers point out a presumed advantage of better or potentially better vascular access longevity with incremental HD, compared to standard HD [9,16,32,53]. Presently there is no evidence that twice-or thrice-weekly needle insertions make a difference in the vascular access longevity.…”
Section: Vascular Accessmentioning
confidence: 99%
See 3 more Smart Citations